Isolation, cloning and sequence analysis of the lactate dehydrogenase gene from Theileria annulata may lead to design of new antitheilerial drugs - Erdemir, A.; Aktas, M.; Dumanli, N.; Turgut-Balik, D. (Czech Academy Agricultural Sciences, 2012)
Theileriosis is a serious animal disease that is transmitted by ticks. Theileria species are tick-borne obligate intracellular protozoan parasites that cause severe and mild infections in their hosts. Two of them, Theileria annulata and Theileria parva, cause lymphoproliferative disease with high mortality and morbidity in cattle commonly known as tropical theileriosis and East Coast fever, respectively. Currently available antiparasitic drugs are effective in animals but animals may remain carriers and treatment is most effective in the early stages of the disease. The isolation, cloning and analysis of lactate dehydrogenase from T annulata was the goal of the present study with the ultimate aim of designing new antiparasitic drugs that will hopefully have a wider mode of action in animals. Blood samples were taken from a four year-old Brown Swiss cow showing signs of acute tropical theileriosis and genomic DNA was extracted following the confirmation of the clinical diagnosis. For the first time, in this study, the lactate dehydrogenase sequence was isolated from from a Theileria species. Following extraction from genomic DNA by PCR the sequence was cloned into the vector pGEM-T easy. Sequencing of the whole gene from both directions indicated that the open reading frame was interrupted by two introns. Several single nucleotide exchanges, deletions and insertions were also observed in the T annulata lactate dehydrogenase sequence compared to the host. The most remarkable difference between the parasite and host enzyme is a five residue insertion in the active site loop region that might be an attractive target for inhibitors of the enzyme. This study opens a new route to further kinetic and structural studies towards the development of novel inhibitors of T annulata lactate dehydrogenase.
Keywords: Theileria annulata; theileriosis; antitheilerials; lactate dehydrogenase; gene cloning